Impacts of climate change on the livelihood of small scale inland open water fishing communities in Chalan Beel area of Bangladesh - Sadekin, Md Nazmus (2019)
Small scale fishing communities (SSF) at the inland open water are among the vulnerable communities in Bangladesh. In addition, fishing activities could provide support to nutrition and food security, poverty alleviation as well as to maintain the sustainable living. However, their contribution is not being recognized by the scholars either nationally or globally. This study assessed the impact of climate change on the small scale fishing communities (SSF) in Chalan Beel area of Bangladesh from the vulnerability perspective, by using two livelihood vulnerability indices. First, by using the method of ‘Livelihood Vulnerability Index’ (LVI), and second on the method of Vulnerability Framework Approach of IPCC (LVI-IPCC method). The main objective of this study is to assess the vulnerability status of the SSF communities due to the climate change. In order to achieve the research objective, data on SSF households from three districts namely Chatmohor, Gurudaspur and Tarash were randomly collected. A total of 352 SSF households were interviewed. Results from the analysis of LVI and LVI-IPCC showed that the SSFs in Tarash faced higher vulnerability than the SSFs in Chatmohor and Gurudaspur. Besides that, this research also found that the SSFs are surrounded by various pressures such as food insufficiency, cash shortage, chronic illness, unsafe water supply, insufficiency of physical asset, lack of access to cash, unable to receive early warning systems on incoming disaster (EWS), and lack of involvement in social networking. Initiatives must be undertaken by the government to help improve the quality of life among the SSF communities, several changes in food policy, health services, informal credit facilities, training and creating more efficient EWS.